THE REVIEW OF EMERGENCY CONCEPT IN ISLAMIC LAW TOWARDS THE FATWA OF THE INDONESIAN ULEMA COUNCIL NO. 14 OF 2021 ON THE USE OF ASTRAZENECA'S COVID-19 VACCINE - Hisan, Khairatun; Rachmawati, Andini (Journal of Indonesian Comparative of SyariÆah Law, 2022)
The increase in the number of patients caused by COVID-19 makes the government try to reduce the number of disease victims with various efforts, one of which is vaccination. One of the vaccines that have been registered to the Indonesian Ulema Council is AstraZeneca vaccine products. Based on MUI fatwa No. 14 of 2021, the vaccine is haram because it uses pork-derived trypsin in its production but become allowed because of emergencies and some of the reasons in the fatwa. Nevertheless, the implementation of the fatwas is less than optimal, one of which is due to the fatwa MUI that is not binding.Some people refuse to use the vaccine because it is considered not currently included in the emergency. After all, other vaccines are halal and pure to use. This research aims to review emergency concepts in Islamic law towards fatwa MUI No. 14 of 2021 on AstraZeneca Product Vaccine Use Law.This research is qualitative research using normative Islamic legal research methods with document study data collection techniques. The data analysis used is inductive.The results of research that has been conducted show that the use of emergency concepts in MUI fatwa No.14 of 2021 Concerning the Use of COVID-19 Vaccine AstraZeneca products have been following the concept of emergency in Islam which includes fears of loss of life and limbs; emergencies that have occurred; there is no other way to avoid an emergency except by performing prohibited acts; the discovery of halal and sacred medicine and the recommendation of a credible doctor; not contrary to the basic Islamic sharia, including safeguarding the rights of others; there is a statement from the Government that the emergency has occurred in a country;and must prevent it with reasonable levels.Keywords: Emergency, MUI Fatwa, Islamic Law, AstraZeneca Vaccine.